2018
DOI: 10.35814/jifi.v16i1.486
|View full text |Cite
|
Sign up to set email alerts
|

Pembuatan, Karakterisasi dan Uji In Vitro Nanopartikel Emas Berbasis Konjugat Gom Arab-Vinkristin

Abstract: Gold nanoparticles (AuNP) are potentially developed as nanomedicine because AuNP is easily synthesized, functionalized, and biocompatible. With gum arabic as a stabilizer, vincristine was conjugated with gold nanoparticles. As a reducing agent, it used 0.02 M Natrium Boro Hidrat (NaBH4)  solution. Gold nanoparticles (AuNP) coated with conjugated gum Arabic (GA) and vincristine (VCR) were successfully synthesized and characterized. The conjugation of GA-VCR and AuNP displayed a narrow hydrodynamic particle size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
1
1
0
1
Order By: Relevance
“…It was shown that nanoparticles with a potential above (+/-) 30 mV are stable in suspension because the surface charge prevents the aggregation of particles (Pertiwi et al, 2018). The zeta potential analysis shows relevant results and confirms the distribution pattern data and the polydispersity index.…”
Section: Discussionsupporting
confidence: 68%
“…It was shown that nanoparticles with a potential above (+/-) 30 mV are stable in suspension because the surface charge prevents the aggregation of particles (Pertiwi et al, 2018). The zeta potential analysis shows relevant results and confirms the distribution pattern data and the polydispersity index.…”
Section: Discussionsupporting
confidence: 68%
“…Tingginya zeta potensial disebabkan oleh adanya gugus karboksil yang diperoleh dari proses oksidasi cincin piranosa (Yan et al, 2017). Zeta potensial merupakan suatu parameter yang menunjukkan adanya gaya tolak antar partikel, umumnya digunakan untuk mengetahui sifat muatan permukaan pertikel (Pertiwi et al, 2018).Semakin tinggi zeta potensial, maka emulsi semakin stabil karena dapat mencegah terjadinya flokulasi. Semakin tinggi konsentrasi selulosa bakteri yang ditambahkan, maka emulsi yang distabilkan dengan ukuran kecil semakin homogen.…”
Section: Penstabil Emulsiunclassified
“…Abinav et al [10] stated that the size of the vesicle diameter is influenced by the amount of cholesterol, the solvent, and the surfactants that form it. [11] stated that the particle size after purification showed smaller results compared to that before purification. This indicates that purification has resulted in pure nanoparticles.…”
Section: Tem (Transmission Electron Microscopy) Observationmentioning
confidence: 99%